Mixture and Exponential Arcs on Generalized Statistical Manifold - Luiza H. F. de Andrade; Francisca L. J. Vieira; Rui F. Vigelis; Charles C. Cavalcante (Entropy, 2018)
In this paper, we investigate the mixture arc on generalized statistical manifolds. We ensure that the generalization of the mixture arc is well defined and we are able to provide a generalization of the open exponential arc and its properties. We consider the model of a φ -family of distributions to describe our general statistical model.